Sustainable Village: Action Research in Kumpulrejo, Argomulyo District, Salatiga City, Central Java - Royke R Siahainenia; Suryo Sakti Hadiwijoyo; Putri Hergianasari (Budapest International Research and Critics University, 2022)
The issue of achieving the Sustainable Development Goals or SGDs as stated in Government Regulations No. 59 of 2017, still reaping various problems related to the position of the Regional Government which is not actively involved in the implementation of the SDGs and is not fully supported by stakeholders. It is necessary to conduct action research with a Participatory Rural Appraisal (PRA) approach. Through surveys and data mining through FGDs related to potentials and problems, the objectives of sustainable development can be identified in order to realize a sustainable village. The results showed that of the 17 SDGs, only 12 SGDs could be implemented at the district level, while the rest were the responsibility of the bureaucrat at the local government level. The potential that can support the achievement of SDGs in Kumpulrejo village is to rely on livestock business, especially cattle.